2017
DOI: 10.3389/fmicb.2017.01829
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Applications of Next Generation Sequencing Technologies as Applied to Food-Related Microbiome Studies

Abstract: The development of next generation sequencing (NGS) techniques has enabled researchers to study and understand the world of microorganisms from broader and deeper perspectives. The contemporary advances in DNA sequencing technologies have not only enabled finer characterization of bacterial genomes but also provided deeper taxonomic identification of complex microbiomes which in its genomic essence is the combined genetic material of the microorganisms inhabiting an environment, whether the environment be a pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
160
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(167 citation statements)
references
References 126 publications
0
160
0
7
Order By: Relevance
“…Selecting regions spanning multiple 16S rRNA gene variable regions and combining information collected over different regions, substantially improved accuracy. In our analysis, the sequences spanning variable regions V4-V6 and V1-V3 yielded the best results, although other studies have recommended other regions [17]. Other confounding factors included amplification efficiency, dominant species present in other samples of the same sequencing run, potential contaminants of the Illumina sequencing workflow, and reference database employed.…”
Section: Discussionmentioning
confidence: 76%
“…Selecting regions spanning multiple 16S rRNA gene variable regions and combining information collected over different regions, substantially improved accuracy. In our analysis, the sequences spanning variable regions V4-V6 and V1-V3 yielded the best results, although other studies have recommended other regions [17]. Other confounding factors included amplification efficiency, dominant species present in other samples of the same sequencing run, potential contaminants of the Illumina sequencing workflow, and reference database employed.…”
Section: Discussionmentioning
confidence: 76%
“…Two other studies have utilized the concept of the heterogeneity spacers (one for V3–V4 primers with Illumina MiSeq for clinical samples and the other using Illumina HiSeq for mock microbial communities and environmental samples) along with multiple in-line indexing; both demonstrated an increased quality of sequences and total number of reads [14,15]. Mock microbial communities in 16S rDNA sequencing acts as potential internal controls to test primer effectiveness against a known bacterial composition [22], and in the study with HiSeq, heterogeneity spacers and triple indexing more accurately identified the expected bacterial composition of the mock community [15]. Our study shows that heterogeneity spacers alone can improve sequence quality in the conserved mouse microbiome compared to our controls, Run 1.…”
Section: Resultsmentioning
confidence: 99%
“…Along with the isolation of cultivable organisms, the role and behavior of microorganisms in food fermentation have been elucidated using advanced techniques involving genomics, transcriptomics, proteomics, and metabolomics (13)(14)(15)(16)(17). The recently developed high-throughput DNA sequencing methods have been employed to find out the different microorganisms and their proportion and succession in complex food fermentations.…”
mentioning
confidence: 99%